Retarded and advanced Green functions for first-order differential equations - Soares de Castro, Antonio [UNESP] (IOP Publishing, 2024)
Retarded and advanced Green functions are examined through the lens of linear first-order ordinary differential equations. They are constructed for a finite interval with emphasis on the imposition of homogeneous Dirichlet boundary conditions at the interval ends. It is shown that both types of Green functions exhibit the property of facilitating solutions.
Keywords: advanced Green function; Dirichlet boundary condition; retarded Green function